Multi-activities jacket / Shahrizad Fitri Mustapha - Mustapha, Shahrizad Fitri (Universiti Teknologi MARA, Perlis, 2017)
The good travelling attire will make people who love to do outdoor activities, feel comfortable when travelling, working or playing with flexible silhouette. The multifunctional elements include waterproof, flexibility, hi-tech, high performance, adjustable, which are suitable for multi activities. More efforts are needed to develop an outdoor jacket that can be used by everyone specially Muslim, so they can perform their solat everywhere and anytime with functional elements. The purposed designs will reduce the physical challenge of donning the jacket, the restrictions on movement while offering safe ambulation likelihood of injury from a fall. The design will be appropriate to overcome weather condition in Southeast Asia with waterproof high-tech fabric and comfortable for user